THE VALIDITY AND RELIABILITY OF THE INSTRUMENT PLANNED BEHAVIOR THEORY IN MEASURING STUDENTS' INTENTIONS TO ENGAGE IN AGRICULTURAL ENTREPRENEURSHIP - Ikhsan Fuady; Yulia Andriani; Moch. Armien Syifaa Sutarjo (Faculty of Animal and Agricultural Science, Diponegoro University, 2023)
The intention of agricultural students to carry out agricultural business is an important thing as a locomotive for the development of agricultural human resources in the future. However, the evaluation of the instrument of Intention to carry out a validated agricultural business is still lacking. This study aims to test and develop a valid and reliable instrument of intention to carry out agricultural business and to determine the level of intention to do agricultural business among students. This research method uses a survey approach which (where the population of this study was 1200 students of the faculty of agriculture in Riau Province, while the sample of this study was 98 respondents.Data analysis to test the validity and reliability using the Rasch modeling test with Winstep. The results of the analysis show that from testing 17 instrument items, which consist of; (a) 5 items instrument attitude, 4 items have good goodfit, while 1 item no 2 is misfit. (b) 4 item instrument subjective norm, where 3 items have good parameters, while 1 item no 9 is misfit, (c) 4 Perceive behavior control instrument items, where 3 items have good parameters, while 1 item no 13 is misfit, (d) 4 instrument intention items, where all items have good parameters or good fit. This value indicates a very good consistency of respondents answers, as well as the quality of the instrument items. For the rating scale test, it was found that respondents were only good enough at distinguishing the rating scale when the scale was from 1 to 4. Based on these findings, it is suggested that in measuring student intentions to do entrepreneurship with the planned behavior theory, it is better to use answer items with 4 scales.